Mutation of a cysteine residue in polyomavirus middle T antigen abolishes interactions with protein phosphatase 2A, pp60c-src, and phosphatidylinositol-3 kinase, activation of c-fos expression, and cellular transformation. - Glenn, G M (1993)
Polyomavirus middle T antigen (MT) interacts with several cellular proteins involved in cell proliferation. MT forms complexes with protein phosphatase 2A (PP2A), pp60c-src (and the related kinases c-fyn and c-yes), and phosphatidylinositol-3 kinase. We made a single point mutation in MT, changing a conserved cysteine residue at position 120 to tryptophan, and characterized the biochemical and biological properties of the mutant (C120W) protein. The mutant MT protein does not associate with PP2A, pp60c-src, or phosphatidylinositol-3 kinase as judged by coimmunoprecipitation and associated phosphatase or kinase activity. The C120W mutant is defective in activation of c-fos expression and in morphological transformation of NIH 3T3 cells.